2018
DOI: 10.1080/19390211.2018.1513433
|View full text |Cite
|
Sign up to set email alerts
|

Citrulline Malate Fails to Improve German Volume Training Performance in Healthy Young Men and Women

Abstract: Background: Citrulline malate (CM) is purported to buffer lactic acid, enhance oxygen delivery, and attenuate muscle soreness. Anaerobic exercise trials with CM have produced conflicting results. Objective: The aim of the current investigation was to test the efficacy of CM on resistance training (RT) with the hypothesis that CM would improve performance. Design: A double-blind, counterbalanced , randomised control trial was utilised to assess the effects of CM on RT. 19 subjects (8 female) (25.7 ± 7.7 years),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 19 publications
1
32
1
Order By: Relevance
“…Therefore, we used the sum of all repetitions performed for all 3 days combined in the analysis. Moreover, in Chappell et al (2018b), the SDs of only Set 1 and Set 10 were reported in the text, whereas all sets were presented in a figure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, we used the sum of all repetitions performed for all 3 days combined in the analysis. Moreover, in Chappell et al (2018b), the SDs of only Set 1 and Set 10 were reported in the text, whereas all sets were presented in a figure.…”
Section: Discussionmentioning
confidence: 99%
“…The literature search resulted in 84 potential studies after removal of duplicates (Figure 1). Following screening, a total of eight studies met the inclusion criteria (Chappell et al, 2018a(Chappell et al, , 2018bda Silva et al, 2017;Glenn et al, 2015;Gonzalez et al, 2017;Pérez-Guisado & Jakeman, 2010;Wax et al, 2015aWax et al, , 2015b. There were a total of 137 participants (26 females) with an age of 25.4 ± 5.4 (mean ± SD) years old.…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, as a commercially available sports supplement, CM has been linked to positive exercise performance outcomes, which are mainly driven by its anti-asthenic effect on muscle fatigue [107,125,126,127,128]. However, there is considerable disagreement on this topic within the literature, since several studies have failed to observe any ergogenic potential of CM regardless of variations in dosing strategies [129,130,131,132].…”
Section: Potential Therapeutic Mediators Of Endothelial Vitality Imentioning
confidence: 99%